THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL INCLUSION AND FINANCIAL BEHAVIOR ON INTENTION IN INVESTING LECTURERS AND EDUCATION PERSONNEL PGRI ADIBUANA UNIVERSITY SURABAYA IN THE CAPITAL MARKET - Yuli Kurnia Firdausia; Siti Samsiyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study was to determine and analyze the effect of financial literacy, financial inclusion and financial behavior on the investment interest of lecturers and education staff at PGRI Adi Buana University, Surabaya. The sample selection technique used is non-probability sampling and the sampling technique is purposive sampling. Data was taken using an online questionnaire in the form of a google form. Data management is carried out using SmartPLS software. Based on the results of the analysis, financial literacy, financial inclusion, financial behavior have a positive and significant influence on investment interest, the influence of both is in the same direction. That is, if the better the financial literacy of the lecturers and education staff at the PGRI Adibuana Surabaya University in the Capital Market, the interest in investing will increase. Keywords: financial literacy, financial inclusion, financial behavior interest in investment.